Preparation of 2,3-Disubstituted 5-Bromo-1H-pyrrolo[2,3-b]pyridine Framework by Fischer Cyclization - Alekseyev, Roman S.; Amirova, Sabina R.; Terenin, Vladimir I. (Synthesis, 2015)
A simple synthesis of some hard-to-reach heterocycles containing 2,3-disubstituted 5-bromo-1H-pyrrolo[2,3-b]pyridine framework by Fisсher indole cyclization in polyphosphoric acid has been developed. A particularly valuable feature of this synthetic route is the possibility to build a 5-bromo-7-azaindole scaffold with alkyl or aryl substituents at positions 2 and 3 from available starting materials.
Keywords: heterocycles; fused-ring systems; pyridines; pyrroles; cyclization; hydrazones